The hot Neptune WASP-166 b with ESPRESSO II: confirmation of atmospheric sodium. Issue 1 (17th March 2022) - Seidel, J V; Cegla, H M; Doyle, L; Lafarga, M; Brogi, M; Gandhi, S; Anderson, D R; Allart, R; Buchschacher, N; Lovis, C; Sosnowska, D
ABSTRACT: The hot Neptune desert, a distinct lack of highly irradiated planets in the size range of Neptune, remains one of the most intriguing results of exoplanet population studies. A deeper understanding of the atmosphere of exoplanets sitting at the edge or even within the Neptune desert will allow us to better understand if planetary formation or evolution processes are at the origin of the desert. A detection of sodium in WASP-166 b was presented previously with tentative line broadening at the $3.4\, σ$ with the HARPS spectrograph. We update this result with two transits observed with the ESPRESSO spectrograph, confirming the detection in each night and the broadened character of the line. This result marks the first confirmed resolved sodium detection within the Neptune desert. In this work, we additionally highlight the importance of treating low-SNR spectral regions particularly where absorption lines of stellar sodium and planetary sodium overlap at mid transit – an important caveat for future observations of the system.